Sarcopenia in Non-Dialysis Chronic Kidney Disease Patients: Prevalence and Associated Factors - de Amorim, Geraldo José; Calado, Cinthia Katiane Martins; Souza de Oliveira, Bruno Carlos; Araujo, Renata Patricia Oliveira; Filgueira, Tayrine Ordonio; de Sousa Fernandes, Matheus Santos; Castoldi, Angela; Vajgel, Gisele; Valente, Lucila Maria; de Lima-Filho, José Luiz; Carvalho, Paulo Roberto Cavalcanti; Souto, Fabricio Oliveira (Frontiers in Medicine, 2022)
Background: Sarcopenia is related to morbidity and mortality in non-dialysis CKD (ND-CKD) patients; however, the pathophysiology of sarcopenia remains unclear. The study aimed to assess the prevalence and factors associated with sarcopenia in ND-CKD individuals. Methods: We cross-sectionally evaluated 139 prevalent ND-CKD patients attending our outpatient clinic at Hospital das Clínicas of the Federal University of Pernambuco, between April and October 2019. Patients older than 18 years old and at G3-G5 CKD stages were included. Hand grip strength, Muscle Mass appendicular Index (APMMI), and Gait Speed (GS) were defined by the standards of the European Working Group on Sarcopenia in Older People (EWGSOP2) guideline. Results: Sarcopenia prevalence was 20.9% and severe sarcopenia 2.9%. Sarcopenic were mostly found in elderly ones (64.8±13.5y vs 54.9±12.8y, p <0.001), revealing lower Body Mass Index (BMI) (26.12(6,79) vs 28.64(6.24), p=0,023), lower phase angle (PhA) (4.50(1,10) vs 5.60(1,20), p <0.001) and lower GS (1.00(0.50) vs 1.40(0.42), p <0.001). They also presented lower serum creatinine levels (2.40(1.50) vs 3.0(1.84), p= 0.032), lower Albumin-to-Creatinine Ratio (ACR) (72.60(1008.30) vs 342.30(1172.13), p=0.039) and Hemoglobin levels (11.45(1.88) vs 12.60(2.40), p= 0.003), and higher levels of C-reactive Protein (CRP) (0.24(0.80) vs 0.03(0.28), p= 0.045) compared to non-sarcopenic. Under Poisson Multivariate Model, PhA (RP: 0.364, CI (95%):0.259 - 0.511, p <0.001), IL-6 (RP: 1.006, IC (95%):1.001 -1.01, p= 0.02) and serum creatinine levels (RP: 0.788, IC (95%):0.641 - 0.969, p= 0.024) were associated with sarcopenia. Conclusions: Sarcopenia predominance was identified in our ND-CKD population, and was associated with lower PhA values, higher IL-6 levels, and lower serum creatinine levels.